PANDANGAN AL-QUR’AN TENTANG PEREMPUAN BEKERJA (HIKMAH DIBALIK SURAT AL-QASHASH) - M. Nurul Qomar (Jurnal Harkat : Media Komunikasi Gender, 2019)
Abstract. The concept of gender is an even more interesting problem when it is associated with the perspective of Islam and the Koran. The role of women in the fabric of life is not in doubt. But there is still debate about permitting women to work outside the home among scholars. To better understand the concept of gender (women in the workplace) attached to Surat al-Qashash (28) verse 23, further analysis is needed using the content analysis approach in the commentary science corridor. Also, the library research approach is used to explore primary and secondary libraries to support this paper. Resulting in the conclusion that the Mufassir mentioned above does not differ significantly in interpreting Surah al-Qashash verse 23. However, the scholars differed in interpreting the father of two women who were assisted by Prophet Musa. b. Economic wisdom that can be learned from Surat al-Qashash verse 23 is that women are allowed to work as long as they can maintain their honor. Also, through this verse, it is understood that for economic activities (mu'amalah), a man is allowed to talk and see the opposite gender.Abstrak  Konsep gender merupakan isu menarik lebih-lebih jika dikaitkan dengan perspektif islam dan al-Qur’an. Peran perempuan dalam tatanan kehidupan tidak diragukan lagi. Namun masih menjadi perdebatan tentang diperbolehkannya perempuan untuk bekerja di luar rumah di kalangan ulama’.  Untuk lebih memahami konsep gender (wanita dalam bekerja) yang melekat pada surat al-Qashash (28) ayat 23 tentu diperlukan analisa lebih lanjut dengan menggunakan pendekatan analisis konten dalam koridor ilmu tafsir.  Selain itu pendekatan library research digunakan untuk menelusuri pustaka baik primer maupun sekunder untuk mendukung tulisan ini. Sehingga menghasilkan simpulan bahwa: a. Para Mufassir yang disebut di atas tidak berbeda jauh dalam menafsirkan surat al-Qashash ayat 23. Akan tetapi para ulama’ berbeda pendapat menafsirkan ayah dari dua perempuan yang ditolong oleh Nabi Musa. b. hikmah ekonomi yang dapat dipetik dari surat al-Qashash ayat 23 adalah diperbolehkan perempuan dalam bekerja, asalkan mampu menjaga kehormatannya, selain itu melalui ayat ini dapat dipahami bahwa atas kegiatan ekonomi (mu’amalah), seorang laki-laki diperbolehkan berbicara dan memandang lawan jenis.